Spondylolysis in active adolescents: Expediting Return to Play - Moeller, J. L.; Rifat, S. F. (The Physician and Sportsmedicine, 2001)
Spondylolysis is the most common identifiable cause of back pain in active adolescents, who often cope with the condition by hoping it will just go away. If the pain is prolonged or severe enough to bring them to a physician, an aggressive work-up for a specific diagnosis should be initiated. History and physical exam findings are suggestive but not diagnostic. Radiographs provide a first look, but other tests (eg, bone scans, CT, and MRI) are necessary to determine the metabolic activity and full extent of any lesions. Conservative therapy, including activity modification, physical therapy, and sometimes bracing, provides pain relief and focuses on return to full activity and prevention of recurrence. THE PHYSICIAN AND SPORTSMEDICINE - VOL 29 - NO.12 - DECEMBER 2001